Pseudo-mono-axial ligand fields that support high energy barriers in triangular dodecahedral Dy() single-ion magnets - Zhang, Ben; Cheng, Zhijie; Wu, Yingying; Chen, Lei; Jing, Rong; Cai, Xingwei; Jiang, Chunhui; Zhang, Yi-Quan; Yuan, Aihua; Cui, Hui-Hui; Li, Zhao-Yang (Chemical science (Cambridge), 2022)
The synthesis of air-stable, high-performance single-molecule magnets (SMMs) is of great significance for their practical applications. Indeed, Ln complexes with high coordination numbers are satisfactorily air stable. However, such geometries easily produce spherical ligand fields that minimize magnetic anisotropy. Herein, we report the preparation of three air-stable eight-coordinate mononuclear Dy( iii ) complexes with triangular dodecahedral geometries, namely, [Dy(BPA-TPA)Cl](BPh 4 ) 2 ( 1 ) and [Dy(BPA-TPA)(X)](BPh 4 ) 2 · n CH 2 Cl 2 (X = CH 3 O − and n = 1 for 2 ; L = PhO − and n = 2 for 3 ), using a novel design concept in which the bulky heptadentate [2,6-bis[bis(2-pyridylmethyl)amino]methyl]-pyridine (BPA-TPA) ligand enwraps the Dy( iii ) ion through weak coordinate bonds leaving only a small vacancy for a negatively charged (Cl ), methoxy (CH 3 O ) or phenoxy (PhO − ) moiety to occupy. Magnetic measurements reveal that the single-molecule magnet (SMM) property of complex 1 is actually poor, as there is almost no energy barrier. However, complexes 2 and 3 exhibit fascinating SMM behavior with high energy barriers ( U eff = 686 K for 2 ; 469 K for 3 ) and magnetic hysteresis temperatures up to 8 K, which is attributed to the pseudolinear ligand field generated by one strong, highly electrostatic Dy-O bond. Ab initio calculations were used to show the apparent difference in the magnetic dynamics of the three complexes, confirming that the pseudo-mono-axial ligand field has an important effect on high-performance SMMs compared with the local symmetry. This study not only presents the highest energy barrier for a triangular dodecahedral SMM but also highlights the enormous potential of the pseudolinear Dy-L ligand field for constructing promising SMMs. Air-stable triangular dodecahedral Dy( iii ) single-ion magnets with pseudo-mono-axial linear ligand fields exhibit high energy barrier exceeding 600 K, which represent the highest energy barrier for mononuclear SMMs with triangular dodecahedron.